Persistent CD38 Expression on CD8+ T Lymphocytes Contributes to Altered Mitochondrial Function and Chronic Inflammation in People With HIV, Despite ART. (1st December 2022) - Mathur, Poonam; Kottilil, Shyamasundaran; Pallikkuth, Suresh; Frasca, Daniela; Ghosh, Alip
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Age-associated comorbidities are higher in people with HIV (PWH) than HIV-negative individuals. This is partially attributed to immune activation and CD38 expression on T cells driving chronic inflammation. However, the exact contribution of CD38-expressing T cells on the proinflammatory response is not completely understood. Methods: CD38-expressing CD8 + T lymphocytes were measured from PWH and HIV-negative individuals. Mitochondrial mass, superoxide content, membrane depolarization of CD4 + and CD8 + T lymphocytes, and cytokine production after HIV(Gag)-specific peptide stimulation from CD38 + CD8 + T lymphocytes of PWH were measured to link biological effects of CD38 expression on cellular metabolism. Results: The frequency of activated CD8 + CD38 + T cells persists in PWH on ART compared with HIV-negative individuals. Higher CD38 expression is associated with mitochondrial biogenesis and HIV(Gag)-specific proinflammatory cytokine production in PWH. Blockade of CD38 results in lower Gag-specific cytokine production. Conclusions: ART only partially reduced HIV-induced CD38 expression on CD8 + T cells. CD8 + CD38 + T cells are highly activated in vivo, and HIV-specific stimulation in vitro augments CD38 expression, contributing to a proinflammatory response despite virologic control with ART. Therefore, CD38 is a potential therapeutic target for mitigating chronic inflammation that likely drives cellular aging, comorbidities, and end-organ disease in PWH.